Cascade three-component composition on polystyrene basis absorbing in visible range and emitting in near IR - Bedrik, A.I.; Doroshenko, A.O.; Gurkalenko, Yu.A.; Shershukov, V.M.; Sulima, O.V. (Functional Materials, 2004)
Design results have been presented for a three-component composition for solar energy conversion into the sensitivity range of Si and GaAs photocells based on polystyrene and polycyclic aromatic organic luminescent compounds. Two possible approaches to selection of concentrations of the components oriented to provide the maximum collection efficienc y of the visible range solar radiation and the optimum conditions of the Foerster non-radiative energy transfer between the intermediate and final components of the cascade compo -sition have been shown to give comparable results and thus do not form an alternative to one another. Представлены результаты дизайна трехкомпонентной композиции для преобразования энергии солнечного излучения в интервал чувствительности Si и GaAs фотоэлементов на основе полистирола и ароматических полициклических органолюминофоров. Показано, что два возможных подхода к подбору концентраций компонентов, ориентированные на обеспечение максимально эффективного сбора излучения в видимом диапазоне и оптимальных условий Ферстеровского безызлучательного переноса энергии между промежуточными и конечными компонентами каскадной композиции, дают сравнимые результаты и, таким образом, не являются альтернативой друг другу. Представлено результати дизайну трьохкомпонентної композиції для конвертування енергії сонячного випромінювання в інтервал чутливості Si та GaAs фотоелементів на основі полістиролу та ароматичних поліциклічних органічних люмінофорів. Показано, що два підходи до добору концентрацій компонентів, орієнтовані на забезпечення максимально ефективного збирання випромінювання у видимому діапазоні і оптимальних умов Ферстерівського безвипромінювального переносу енергії між проміжними та кінцевими компонентами каскадної композиції, дають порівняні результати і, отже, не є альтернативою один одному.